HIGHER PEDAGOGICAL EDUCATION AND EMPLOYERS: PRINCIPLES OF COLLABORATION - E. A. OPFER (Высшее образование в России)
The article presents the principles of collaboration between higher pedagogical education and employers. The system of the principles works for improving the quality of higher pedagogical education and its ability to meet the demand of all the stakeholders. The following principles are grounded: scientific basis of collaboration between pedagogical university and employers (systemcreating), openness of pedagogical university education space, stakeholders’ personal position in educational process, integration of innovations and traditions in the process of teacher training, the unity of regional education space, and the corporate unity in the process of identification of stakeholders’ demand.